Responding to the need of the Society: Nepal Ambulance Service - Gongal, R; Vaidya, P (Journal of Institute of Medicine Nepal, 2013)
DOI: http://dx.doi.org/10.3126/joim.v34i1.9114 Journal of Institute of Medicine, April, 2012; 34:1 1